2000
DOI: 10.1037/0033-3204.37.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mentoring in clinical versus experimental doctoral programs: Survey findings, implications, and recommendations.

Abstract: Previous research suggests that mentorships are quite important in the development of junior professionals in a range of fields, including psychology. Yet some evidence suggests that clinical doctoral students may be less frequently mentored by graduate faculty than other psychology doctoral students. Results of a survey of clinical and experimental psychology doctorates who earned the degree in four distinct time frames from 1945 to the present indicated that clinical PhDs (53%) were indeed less likely than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 41 publications
2
59
1
1
Order By: Relevance
“…Since 1945, clinical psychology doctoral students have been significantly less likely (53%) than nonclinical (experimental) doctoral students (69%) to be mentored (Johnson, Koch, et al, 2000), and among recent clinical psychology graduates, PsyDs (56%) are significantly less likely than PhDs (73%) to be mentored (Clark et al, 2000).…”
Section: How Prevalent Is Mentoring In Psychology?mentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1945, clinical psychology doctoral students have been significantly less likely (53%) than nonclinical (experimental) doctoral students (69%) to be mentored (Johnson, Koch, et al, 2000), and among recent clinical psychology graduates, PsyDs (56%) are significantly less likely than PhDs (73%) to be mentored (Clark et al, 2000).…”
Section: How Prevalent Is Mentoring In Psychology?mentioning
confidence: 99%
“…Mentoring is a personal relationship in which a more experienced (usually older) faculty member or professional acts as a guide, role model, teacher, and sponsor of a less experienced (usually younger) graduate student or junior professional. A mentor provides the protégé with knowledge, advice, challenge, counsel, and support in the protégé's pursuit of becoming a full member of a particular profession (Clark et al, 2000;Johnson, Koch, Fallow, & Huwe, 2000 (e.g., teaching, advising, supervising, counseling, friendship), yet the whole is clearly more than the sum of these parts.…”
Section: Toward a Definition Of Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Within academia, student-faculty relationships tend to be more formalized, with the most common type being the advisor-advisee relationship in graduate school (Schlosser & Gelso, 2001;Schlosser, Knox, Moskovitz, & Hill, 2003;Schlosser, Talleyrand, Lyons, Kim, & Johnson, 2005). Research has shown that students almost always have an advisor (Schlosser & Gelso, 2001), but only 50 to 66 percent report having a mentor (Atkinson, Casas, & Neville, 1994;Clark, Harden, & Johnson, 2000;Cronan-Hillix, Davidson, Cronan-Hillix, & Gensheimer, 1986;Hollingsworth & Fassinger, 2002;Johnson, Koch, Fallow, & Huwe, 2000). So, while our focus is on mentoring, it is important to note that many mentors are also advisors, and researchers have speculated that positive advising relationships and mentoring relationships are quite similar (Schlosser & Gelso, 2001;Schlosser & Gelso, in press).…”
mentioning
confidence: 99%
“…Trainees develop enhanced professional skills, greater confidence, and increased scholarly productivity. [7][8][9] Faculty mentors gain increased academic productivity and accelerated professional recognition. 1,10,11 The goal of this study was to examine the effectiveness of 2 interventions on increasing the number of mentor relationships in graduate medical education (GME) programs at Stanford University Medical Center and Lucile Packard Children's Hospital.…”
Section: Introductionmentioning
confidence: 99%